The Effect of Project Based Learning on Changes in Self-regulated learning - Nadyati Putri; Febrinna Marchy; Dadan Dasari; Cut Nadia Rachmi (Universitas Teknokrat Indonesia, 2025)
This study aims to examine the effect of Project Based Learning (PjBL) implementation on students' self-regulated learning in mathematics learning. Using a quasi-experimental design with Nonequivalent Pretest-Posttest Control Group Design, this study involved two classes of VIII grade students at SMP Negeri 5 Bandung. One class acted as an experimental class with the application of PjBL, while the control class used conventional learning with a scientific approach. Data were collected through pretest and posttest and attitude scale questionnaire, then processed using Mann-Whitney U nonparametric statistical test. The average N-gain of self-regulated learning in the PjBL class was 0.23, which was significantly higher than the conventional class's 0.16, according to the data. In conclusion, PjBL is effective in increasing students' self-regulated learning compared to conventional learning methods. Based on these findings, it is recommended that PjBL be implemented in the curriculum to support the development of students' self-regulated learning.